Highly potential chemotherapeutic agent derived from schiff base complexes / Siti Solihah Khaidir ... [et al.] - Khaidir, Siti Solihah; Ahmad, Shahrul Nizam; Kassim, Karimah; Abd Karim, Nurul Huda (2022)
The synthesis, characterization, and cytotoxicity studies of Schiff base with copper (II), nickel (II), cobalt (II) and zinc (II) metal salts are reported here. The ligands were synthesized by condensation reaction of appropriate carbonyl and amine compounds. The reactions were carried out in the presence of ethanol and some of the reactions were carried out in the mixture of ethanol and chloroform. Schiff base ligands and complexes were synthesized via microwave-assisted synthesis. The complexes were characterized by means of elemental analysis (EA), magnetic susceptibility (MSB), molar conductance, fourier transform infrared (FT-IR) spectroscopy, nuclear magnetic resonance (1H NMR and 13C NMR) spectroscopy, UV-Visible spectroscopy, and thermogravimetric analysis (TGA). IR spectra of the complexes show a shifting of ν(C=N) and ν(C-O) peaks to a lower frequency as well as the appearance of new M-N and M-O peaks indicating the metal ion was bonded to ONNO donor atoms. The binding mode and interaction of ligand and complexes with porcine and Calf DNA were determined by UV–Vis DNA titration technique. The investigation revealed that all complexes showed a higher binding constant, Kb. The metal complexes and their corresponding ligands were tested against colon cancer cell lines (HCT116). It was found that the tetranuclear copper complex is the most potent chemotherapeutic agent.